2019
DOI: 10.1002/chem.201904484
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Prerequisite Formation of Phenoxyl Radicals in Radical‐Mediated Peptide Tyrosine Nitration In Vacuo

Abstract: The elementary mechanism of radical‐mediated peptide tyrosine nitration, which is a hallmark of post‐translational modification of proteins under nitrative stress in vivo, has been elucidated in detail by using an integrated approach that combines the gas‐phase synthesis of prototypical molecular tyrosine‐containing peptide radical cations, ion–molecule reactions, and isotopic labeling experiments with DFT calculations. This reaction first involves the radical recombination of .NO2 towards the prerequisite phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Finally, in a very elegant example showcasing the power of IMR to uncover hard‐to‐obtain mechanistic insights, the Chu group showed that phenoxyl radicals are the pre‐requisite intermediates in peptide tyrosine nitration by • NO 2 (Lai et al, 2020). By studying the radical cation of the tetrapeptide GGYG the authors saw the evidence of a covalent insertion of NO 2 into the aromatic ring of the Tyr residue (Figure 23):…”
Section: Imr Of Radical Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in a very elegant example showcasing the power of IMR to uncover hard‐to‐obtain mechanistic insights, the Chu group showed that phenoxyl radicals are the pre‐requisite intermediates in peptide tyrosine nitration by • NO 2 (Lai et al, 2020). By studying the radical cation of the tetrapeptide GGYG the authors saw the evidence of a covalent insertion of NO 2 into the aromatic ring of the Tyr residue (Figure 23):…”
Section: Imr Of Radical Ionsmentioning
confidence: 99%
“…(A) MS spectrum after the ion–molecule reaction of • NO 2 towards [GGYG] •+ ( m /z 352), and B) the CID spectrum of NO 2 [GGYG] + ( m / z 398). (from reference: Lai et al, 2020). [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Imr Of Radical Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosyl radicals are relatively stable π‐radicals that play a paramount role in the long‐distance electron transfer found in many important biological systems such as Photosystem II, ribonucleotide reductase (RNR), and cytochrome c oxidase [6] . In Photosystem II, an unclustered, single water molecule is involved in hydrogen atom transfer (HAT) from a tyrosine residue (Tyr161) and stabilization of resulting tyrosyl radicals (Figure 1a) [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Identifying ortho protein tyrosine nitration (PTN, Scheme S1) is important because this modification is a known biomarker of neurodegenerative disorders and age-related diseases. 23 Furthermore, because nitration is both regioselective and highly selective for specific tyrosyl residues, 24 detection of further endogenous nitration sites may aid in determining the factors that promote nitration. Previously, such identification has been challenging because of the low stoichiometry of PTN modification (estimated occurrence: <0.001%).…”
mentioning
confidence: 99%